Odd Inverse Power Generalized Weibull Generated Family of Distributions: Properties and Applications. (9th November 2021) - Al-Moisheer, A.S.; Elbatal, I.; Almutiry, Waleed; Elgarhy, Mohammed
Abstract : A novel family of produced distributions, odd inverse power generalized Weibull generated distributions, is introduced. Various mathematics structural properties for the odd inverse power generalized Weibull generated family are computed. Numerical analysis for mean, variance, skewness, and kurtosis is performed. The new family contains many new models, and the densities of the new models can be right skewed and symmetric with "unimodal" and "bimodal" shapes. Also, its hazard rate function can be "constant, " "decreasing, " "increasing, " "increasing-constant, " "upside-down-constant, " and "decreasing-constant." Different types of entropies are calculated. Some numerical values of various entropies for some selected values of parameters for the odd inverse power generalized Weibull exponential model are computed. The maximum likelihood estimation, least square estimation, and weighted least square estimation approaches are used to estimate the OIPGW-G parameters. Many bivariate and multivariate type models have been also derived. Two real-world data sets are used to demonstrate the new family's use and versatility.